Deepening the scope of the "economic model": Functionalities, structures, mechanisms, and institutions - Stefan P. Schleicher (WWWforEurope, 2015)
By responding to the warning voices about the failure of mainstream economics to provide policy advice to seemingly well-known problems as manifest in the ongoing economic crises, we put forward the proposition that the majority of deficiencies in this discipline results from two self-imposed restrictions. The first restriction refers to the limited scope in the perception of economic activities by focusing mainly on reproducible goods (including services) and a very few resources, as human capital and by production reproducible capital. The second restriction results from the interwoven relationships that describe economic structures and the coordinating mechanisms which operate on these structures by postulating market relationships that quite often turn out to be too simplistic or non-existing. We propose therefore two conceptual extensions. The first extension opens up the scope of economic activity both by introducing the functionalities of well-being and an extended list of stocks and flows of resources. The second extension separates the description of economic structures from the mechanisms that operate on them, which may be market or non-market based. Furthermore we will demonstrate how these extensions can be made operational in the context of analyzing the transition of energy systems.
Keywords: 330; Wirtschaftsmodell; Wirtschaftspolitik; Wirkungsanalyse